The Responsibilities of the Board of Directors of a Limited Liability Company for Workers Who Have Work Accidents - Alya Rihadatul Aisy; Aminah Aminah (Law Development Journal, 2023)
This study aims to determine the fulfillment of responsibilities in legal protection efforts given by Limited Liability Companies (Directors) to workers who experience work accidents. The formulation of the research problem looks at the responsibilities and rights possessed by workers, as well as the obligations of the Limited Liability Company in guaranteeing its workers who experience work accidents as well as those who are not registered for employment guarantees and death benefits. The research used is the Normative Juridical research method. While the conclusion from this study is that the directors are responsible for the management of a limited liability company, morally entrepreneurs have an obligation to increase protection, and the company is obliged to provide guarantees to workers so that the risks of harm and potential for risks in the work environment and the rights and obligations of each party are fulfilled. It needs to be known as a form of protection for all workers to fulfill company obligations and workers' rights, and maintain and avoid things that are not desirable in the future by providing a sense of security in the form of adequate facilities and employment guarantees to all employees/workers.